Clinical features of domains of somatized disorder and mechanisms of somatization - Mamchur Олександр; Yuryeva Людмила (Psychosomatic Medicine and General Practice, 2019)
This publication is a fragment of work on the analysis of clinical and psychopathological features of somatoform abnormalities in patients with psychotic and non-psychotic disorders in order to substantiate ways of optimizing the diagnosis of somatoform disorders in patients with mental disorders of different genesis, taking into account the pathogenetic mechanisms of somatization and the development of complex medical and rehabilitation measures.